PENGARUH FAKTOR INTERNAL, EKSTERNAL, DAN LAYANAN TRANSAKSI DIGITAL BANK TERHADAP PROFITABILITAS - Anastasia, Marizka Distya; Munari, Munari (E-Jurnal Manajemen, 2021)
One of the important factors for banking is financial service providers who describe the bank to perform performance as measured by profitability. Factors that cause changes in bank profitability can be seen from internal factors as well as external factors as well as the application of technology. This study aims to analyze, test, and prove the effect of CAR, NPL, LDR, BOPO, company size, inflation, economic growth, internet banking transactions, and mobile banking transactions on the profitability of commercial banks listed on the Indonesia Stock Exchange in 2015-2019. This study uses quantitative methods with secondary data obtained through bank financial reports available on the IDX and the website of the Badan Pusat Satistik (BPS) related to inflation and economic growth data. Determination of the sample using purposive sampling technique in order to obtain 6 commercial banks to be researched. Technical analysis of the data using multiple linear regression. The results showed that CAR has a significant positive effect on profitability, while BOPO, economic growth, and mobile banking transactions have a significant effect on profitability. However, NPL, LDR, company size, inflation, and internet banking transactions have no effect on profitability. Keywords: Internet banking; mobile banking; profitability